2020
DOI: 10.1016/j.omtm.2020.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Strategies of Cationic Liposomes for Cancer Gene Therapy

Abstract: Cationic liposomes (CLs) have been regarded as the most promising gene delivery vectors for decades with the advantages of excellent biodegradability, biocompatibility, and high nucleic acid encapsulation efficiency. However, the clinical use of CLs in cancer gene therapy is limited because of many uncertain factors in vivo . Extracellular barriers such as opsonization, rapid clearance by the reticuloendothelial system and poor tumor penetration, and intracellular barriers, including end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(115 citation statements)
references
References 190 publications
(313 reference statements)
1
97
0
Order By: Relevance
“…Recent developments in gene therapy over the last decade or so has drawn the renewed attention of many companies and researchers to the use of viral vectors (using various virus systems, e.g., adenovirus [44][45][46][47][48] and AAV [49][50][51]), along with completely synthetic particles, involving liposomes and nanoparticles [52][53][54][55][56][57], as drug (nucleic acid) delivery systems. Initially, interest in this area was predominately concerned with the delivery of DNA therapeutic material, however, interest has widened to include the use of RNA therapeutics [58] such as interference ribonucleic acids, RNAi [59,60], and messenger ribonucleic acids, mRNA [61,62] along with gene editing payload material [63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in gene therapy over the last decade or so has drawn the renewed attention of many companies and researchers to the use of viral vectors (using various virus systems, e.g., adenovirus [44][45][46][47][48] and AAV [49][50][51]), along with completely synthetic particles, involving liposomes and nanoparticles [52][53][54][55][56][57], as drug (nucleic acid) delivery systems. Initially, interest in this area was predominately concerned with the delivery of DNA therapeutic material, however, interest has widened to include the use of RNA therapeutics [58] such as interference ribonucleic acids, RNAi [59,60], and messenger ribonucleic acids, mRNA [61,62] along with gene editing payload material [63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, BP1001 is uniquely different from other liposomal oligo formulations, which typically utilize positively charged lipids to bind to the negatively charged oligonucleotides [ 135 , 136 ]. The neutral charge of DOPC lipids reduces liposomes’ interactions with charged plasma proteins, thereby increasing blood circulation time and cellular uptake [ 137 , 138 ]. Additionally, DOPC is non-immunogenic and has a very low fatty acid chain melting temperature (below freezing point), making it highly desirable for drug delivery.…”
Section: Bp1001: Liposomal P-ethoxy-grb2 Asomentioning
confidence: 99%
“…Research by Hattori et al [ 55 ] confirmed that the type of cationic lipids has a huge impact on the biological distribution and knockdown efficiency of siRNA in vivo. In other words, the therapeutic effect of CLs is determined by the rational design of lipid composition [ 56 ].…”
Section: Protective Carriers For Sirna Deliverymentioning
confidence: 99%